Evaluation of the Genotoxic Potential against H2O2-Radical-Mediated DNA Damage and Acute Oral Toxicity of Standardized Extract of Polyalthia longifolia Leaf - L. Jothy, Subramanion; Yeng, Chen; Kanwar, Jagat R; Sasidharan, Sreenivasan (Hindawi Publishing Corporation, 2013)
Medicinal plants have been used in medicoculturally diverse countries around the world, where it is a part of a time-honoured tradition that is respected even today. Polyalthia longifolia leaf extract has been previously reported as an efficient antioxidant in vitro.Hence, the genotoxic effects of P. longifolia leafwere investigated by using plasmid relation, comet, andAllium cepa assay. In the presence of ∙OHradicals, theDNAin supercoilwas start nicked into open circular form,which is the product of the single-stranded cleavage of supercoil DNA and quantified as fragmented separate bands on agarose gel in plasmid relation assay. In the plasmid relation and comet assay, the P. longifolia leaf extract exhibited strong inhibitory effects against H2O2-mediated DNA damage. A dose-dependent increase of chromosome aberrations was also observed in the Allium cepa assay. The abnormalities scored were stickiness, c-mitosis, bridges, and vagrant chromosomes. Micronucleated cells were also observed at the interphase. The results of Allium cepa assay confirmed that the methanol extracts of P. longifolia exerted no significant genotoxic or mitodepressive effects at 100